Cultural intelligence, international experience and early internationalization: An essay on connecting constructs - Roecker, Rejane; Floriani, Dinorá Eliete (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
This article aims to discuss how the constructs of international experience, cultural intelligence, and early internationalization are connected, according to their respective theoretical perspectives. The international business literature has not addressed how managers' international experience generates cultural intelligence and drives early internationalization, considering aspects of the entrepreneur and the organization. It is observed that the international experience results in three characteristics: cultural knowledge, cultural skills, and metacognition. The manager's characteristics can be incorporated into the proposed model, demonstrating the connection between international experience, cultural intelligence, and early internationalization. They encompass the manager's international orientation, faster recognition of international opportunities, and faster internationalization.